SIGNIFICANCE OF SULTAN MIR HAYDAR MAUSOLEUM IN UZBEKISTAN - Abdiev Izzatbek Riskibaevich (American Journals Publishing, 2023)
This article clarifies the structure and history of the architectural monument of Sultan Mir Haydar which was located in the Kasbi district of the Kashkadarya region, including the life path and names of His Highness Sultan Mir Haydar.
Keywords: Sultan Mir Haydar, mausoleum, mosque, Great Silk Road, Amir Temur, courtyard, hadith, descendant.